Pengaruh Persepsi Kemudahan dan Kepercayaan Terhadap Keputusan Pembelian Menggunakan Dompet Digital Shopeepay - Haya Maharani Lubis; Netti Nurlenawat; Dexi Triadinda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The rapid development of technology provides convenience for its users. Technological advances that compete with finance create changes in people's behavior in making transactions on online purchases. This research aims to find out: 1) The effect of perceived convenience on trust in using shopeepay, 2) The effect of perceived convenience on purchasing decisions using shopeepay, 3) The effect of trust on purchasing decisions using shopeepay, 4) The effect of perceived convenience on purchasing decisions using shopeepay through trust, 5) The effect of perceived convenience and trust simultaneously on purchasing decisions. The research method is explanatory survey with a quantitative approach. The sampling technique used purposive sampling with a sample size of 96 respondents. The data analysis technique is path analysis. Perceived convenience has a positive and significant effect on trust. Partially, perceived convenience has a positive and significant effect on purchasing decisions. Partially, trust has a positive and significant effect on purchasing decisions. There is an indirect influence between perceived convenience on purchasing decisions mediated by trust. Perceptions of convenience and trust have a simultaneous and significant effect on purchasing decisions.